2019
DOI: 10.3390/en12244703
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Onshore Wind Repowering in Germany under Policy Regime Changes: A Real Options Analysis

Abstract: In this paper, we investigate capacity expansion, the technological development of wind turbine generators, and the merits of onshore wind repowering in Germany. We analyze the regulatory framework that is presently in place and its impact on the profitability of the onshore wind parks commissioned under previous regulatory frameworks. The optimal timing of repowering under today’s market premium model is scrutinized. Repowering in a market without subsidies for onshore wind energy is also evaluated. In the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…"Replanting" (discussed in [8]) and "end-of-life extensions" (Table 3) did not find resonance in the offshore wind literature. There were 280 publications on wind and repowering on Scopus with the potential to transfer expertise from onshore to offshore wind, as the repowering of onshore wind farms is already more widespread (see, e.g., [207][208][209][210][211][212][213][214][215][216]).…”
Section: Repoweringmentioning
confidence: 99%
“…"Replanting" (discussed in [8]) and "end-of-life extensions" (Table 3) did not find resonance in the offshore wind literature. There were 280 publications on wind and repowering on Scopus with the potential to transfer expertise from onshore to offshore wind, as the repowering of onshore wind farms is already more widespread (see, e.g., [207][208][209][210][211][212][213][214][215][216]).…”
Section: Repoweringmentioning
confidence: 99%
“…Referring to policies and the design of regulatory elements for managing equipment at end-of-life, Madlener et al [22] investigate the optimal timing of onshore wind repowering under the premium regime in Germany. Invernizzi et al [23] provide foundations for incorporating circular economy principles into an integrated decommissioning policy to promote sustainable management in energy infrastructures.…”
Section: Of 23mentioning
confidence: 99%
“…Moreover, they concluded that laws had to be updated in parallel with technology or be mitigated with instruments of subsidies in order to favor repowering. Recently, Madlener et al analyzed the evolution of the regulatory framework of RES laws in Germany, and proposed a model to determine the optimal moment to repower according to the EEG ('Erneuerbare Energien Gesetz', Renewable Energy Law 2017), which also considers technical and economic factors [64]. Economically, early repowering is more beneficial, and it is highly influenced by the rate granted at the beginning of the project.…”
Section: Multi-category Analysismentioning
confidence: 99%
“…Revised papers by country and technology. Period (2000-2021).Germany[38,39,[44][45][46]54,58,60,64,71,96,101,102] …”
mentioning
confidence: 99%